TRAINING IN MONITORING TODDLER GROWTH AND DEVELOPMENT FOR POSYANDU CADRES IN MASANGAN KULON VILLAGE, SIDOARJO - Catur Wulandari; Farah Nuriannisa; Anugrah Linda Mutiarani; Teguh Herlambang (Universitas Airlangga, 2023)
Health cadres are an extension of the health workers at the Community Health Center who take part in the monitoring program for the growth and development of toddlers. Cadre development is an important means of improving cadre skills in monitoring the growth and development of toddlers. This activity aims to increase the capacity of cadres in optimally monitoring the growth and development of toddlers. The respondents in this activity were 60 posyandu cadres. The training provided includes measuring height or body length, body weight, LiLA of toddlers, and detecting toddler development using KPSP. Respondents were given a pre-post test to measure the increase in cadres' ability to monitor the growth and development of toddlers. As many as 86.7% of posyandu cadres were able to monitor the growth of toddlers correctly after attending the training. As many as 45% of posyandu cadres were able to properly monitor the development of toddlers using KPSP after attending training. Training related to monitoring the growth and development of toddlers needs to be provided periodically so that cadres' abilities continue to increase.